2002
DOI: 10.1056/nejmoa012864
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD3 Monoclonal Antibody in New-Onset Type 1 Diabetes Mellitus

Abstract: Treatment with hOKT3gamma1(Ala-Ala) mitigates the deterioration in insulin production and improves metabolic control during the first year of type 1 diabetes mellitus in the majority of patients. The mechanism of action of the anti-CD3 monoclonal antibody may involve direct effects on pathogenic T cells, the induction of populations of regulatory cells, or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
829
6
16

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,111 publications
(885 citation statements)
references
References 36 publications
20
829
6
16
Order By: Relevance
“…An influence of age was not detected in the trial conducted by Herold et al This might be related to the different age range (7.5-30 years) or distribution in their study, or to its shorter follow-up [4,6]. The present finding that the effects of ChAglyCD3 are much more pronounced in younger patients can be explained by an age-dependency of the insulitis process.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…An influence of age was not detected in the trial conducted by Herold et al This might be related to the different age range (7.5-30 years) or distribution in their study, or to its shorter follow-up [4,6]. The present finding that the effects of ChAglyCD3 are much more pronounced in younger patients can be explained by an age-dependency of the insulitis process.…”
Section: Discussioncontrasting
confidence: 60%
“…This treatment was also tested in recent-onset type 1 diabetic patients using humanised Fc mutated anti-human CD3 antibodies [4][5][6], which are less mitogenic and cytokinereleasing than murine FcR-binding CD3 antibodies such as muronomab CD3 (orthoclone OKT3) [7][8][9]. In a Phase 1/2 trial, a CD3-specific monoclonal antibody, hOKT3γ1 (AlaAla), was administered for 2 weeks [4,6]. In our Phase 2 placebo-controlled trial, the aglycosylated recombinant ChAglyCD3 was administered for six consecutive days [5].…”
Section: Introductionmentioning
confidence: 99%
“…A short treatment with humanised monoclonal anti-CD3 antibodies preserves beta cell function in recent-onset type 1 diabetes [2,3], particularly in individuals with residual beta cell function ≥25% of controls [3]. This opens perspectives for immunomodulatory interventions in the late preclinical phase where beta cell function is likely to be even better preserved [4] and where anti-CD3 antibodies have also shown efficacy in animal models [5].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the preclinical studies that showed efficacy in murine models of diabetes even at the time of presentation with hyperglycemia and the acceptable adverse event profile that was seen in studies of renal and renal/pancreas allograft recipients and patients with refractory psoriatic arthritis (19,20), we initiated a phase I/II randomized controlled study to study the safety and efficacy of a single course of treatment with hOKT3γ1(Ala-Ala) on the loss of insulin production over 2 years in patients with new onset type 1 diabetes. We previously reported that the mAb prevented the loss of insulin production over the 1st year after diagnosis of type 1 diabetes in the initial one-half of the study entrants (21). In this study, we provide our findings from the complete study participants who were followed for 2 years.…”
mentioning
confidence: 99%